The wheel of Doll - Ames, Jonathan (Ames Jonathan. Doll series, 2022)
Although badly scarred and down to his last kidney after the previous caper, Happy Doll is back in business. When a beguiling young woman turns up at his door, it's Doll's past that comes knocking. Mary DeAngelo is searching for her estranged mother, Ines Candle--a singular and troubled woman Doll once loved. The last he'd seen her she'd been near-death: arms slit like envelopes. Although she survived the episode, she vanished shortly thereafter. Now, years later, Mary claims Ines is alive and has recently made contact--messaging her on Facebook and calling her from a burner phone--only to disappear once again. Although his psychoanalyst would discourage it, Doll takes the case, desperate to see Ines again. But as the investigation deepens, there are questions he can't shake. What's led the flighty Ines to reappear? Is Mary only relaying half the truth? And who is Mary's strange and mysterious husband? In this novel, Happy travels through L.A., Washington, Oregon and back again--a journey that gets wilder and woolier with each turn. An irreverent and inventive mystery.